NATIONAL IDENTITY IN HIGH SCHOOL HISTORY BOOK - Sumaludin, M. Maman (Universitas Pendidikan Indonesia, 2017)
This study aims to analyze national identity in history textbook at the level of senior high school. History textbooks contain material that influenced by ideology which closely related to national identity. The ideology is shown as a manifestation of the nation through history textbooks. The method used to find out the discourse of national identity in textbooks using Fairclough critical discourse analysis to analyze the contents and discourses of national identity in history textbooks. The results showed that the influence of the government is very strong on sample of history textbook. The influence is seen from the planting of the state ideology as a form of government obligation in an effort to shape the character and personality of the nation. In addition, it is done to strengthen national identity through education.